Pengembangan Lembar Kerja Peserta Didik (LKPD) pada Materi Geometri berbasis Budaya Jambi untuk Meningkatkan Kreativitas Siswa - Ayu Wandari; Kamid Kamid; Maison Maison (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2018)
This research aims to describe the process of students’ worksheet development for math subjects and find out the quality of students’ worksheets produced for geometry subject which is based on Jambi culture. This research applies research and development (R&D) method to produce a particular product. The development model applied in this research is ADDIE with 5 stages, analysis, design, development, implementation, evaluation. Subjects of this research are two validators which consist of validator of material expert, validator of design expert and students of a junior high school in grade VII. Data collected in this research are qualitative and quantitative data. Instruments used in this research are a questionnaire and a final test. The result of this study shows the development of students’ ability in mathematical representation at high category based on a gain test with 0,7 in high criteria. The result of the analysis from the questionnaire shows > 80% positive. It can be concluded that students’ worksheet for math subject is good and can improve students’ creativity. Therefore, students’ worksheet can be effectively used by both teachers and students in geometry subject.